A combined diabetes and continuous glucose monitoring education program for adults with type 2 diabetes - Nanna Lind; Merete Bechmann Christensen; Kirsten Nørgaard (Elsevier, 2024)
Objective: The lack of descriptions for education programs in studies evaluating the efficacy of continuous glucose monitoring (CGM) compared to blood glucose monitoring (BGM) for individuals with T2DM makes it difficult to compare results across trials. This study aimed to develop and evaluate a new education program for adults with insulin-treated T2DM and HbA1c ≥58 mmol/mol (7.5 %) initiating CGM. Methods: A 3-h education program was created to provide information on diabetes self-management and CGM or BGM based on international guidelines and a pre-evaluation based on user needs assessment. Questionnaires were used to post-evaluate participant-rated benefits from the program. Results: Seven individuals attended a user needs assessment of the program and 96 participated in the final education program (61.5 % men, mean age 61 (59.5;63) years, mean diabetes duration 18.2 (16.9;19.5) years, and median HbA1c 69 (63-78)mmol/mol (8.5 (7.9-9.3)%). Benefit from this program was rated good/very good by 95.5 % with no statistically significant difference between glucose monitoring groups. Conclusions: This study presents a new well-received education program for T2DM for both the CGM and BGM group. Innovation: The description of the development process and the education provided for both glucose monitoring groups may be useful for CGM initiation in clinics and trials.